A case study of fishbone sequential diagram application and ADREP taxonomy codification in conventional ATM incident investigation - Liang Cheng, Schon Z. Y.; Arnaldo Valdés, Rosa María; Gómez Comendador, Victor Fernando; Sáez Nieto, Francisco Javier (MDPI, 2019)
This paper aims to present the application of a fishbone sequential diagram in air traffic management (ATM) incident investigations performing as a key connection between safety occurrence analysis methodology (SOAM) and accident/incident data reporting (ADREP) approaches. SOAM analysis is focused on organizational cause detection; nevertheless, this detection of individual causes from a complete incident scenario presents a complex analysis, and even more, the chronological relationship between causes, which is lacking in SOAM, should be tracked for post-investigation analysis. The conventional fishbone diagram is useful for failure cause classification; however, we consider that this technique can also show its potential to establish temporal dependencies between causes, which are categorized and registered with ADREP taxonomy for future database creation. A loss of separation incident that occurred in the Edmonton area (Canada) is used as a case study to illustrate this methodology as well as the whole analysis process.
Keywords: ATM incident analysis; fishbone sequential diagram; ADREP taxonomy; SOAM